Increase in cognitive function is seen in many single-operated pediatric patients after epilepsy surgery. (October 2020) - de Knegt, Victoria Elizabeth; Hoei-Hansen, Christina Engel; Knudsen, Marianne; Jakobsen, Anne Vagner; Mûller, Elisabeth; Thomsen, Katrine Moe; Jespersen, Bo; Uldall, Peter Vilhelm; Børresen, Malene Landbo
Highlights: Epilepsy surgery allows for IQ gains. Preoperative seizure frequency is a predictor of IQ change after surgery. Single-operated patients have the best cognitive outcome after surgery. Abstract: Purpose: The recurrent seizures of pediatric drug-resistant epilepsy (DRE) are known to impair brain development and can lead to a loss in cognitive functioning. Surgery is increasingly being used to treat children with DRE. This study investigates the pre- and postoperative cognitive function in a pediatric epilepsy surgery cohort as well as predictive determinants of change in intelligence quotient (IQ) following surgery. Methods: A consecutive series of 91 Danish children who underwent focal resective epilepsy surgery between January 1996 and December 2016 were included. All underwent preoperative cognitive evaluation and were reevaluated at 1-year and/or 2-year follow-up. Single-operated and multi-operated patients were examined separately. Results: 79 of 91 patients were single-operated. Single-operated patients received less anti-epileptic drugs (AED) and experienced a decrease in seizure frequency postoperatively, p < 0.001 . IQ increased postoperatively (IQ change ± standard deviation: 3.3 ± 14.0), p < 0.05 . High preoperative seizure frequency was a significant predictor for decreased IQ, p < 0.01 . Multi-operated patients did not experience a reduction in AED treatment. Surgery and continued AED treatment did, however, result in significantly better seizure control, p < 0.01 . IQ remained unchanged in multi-operated patients. Conclusion: Epilepsy surgery allowed for IQ gains in single-operated patients. Preoperative seizure frequency was a significant predictor of IQ change following surgery. Interactions between other, not included, possible predictors remain to be examined. Single-operated patients had the best cognitive outcome. The inclusion of a non-surgical control group is needed to assess the extent of the beneficial effects of surgery on cognitive ability.